Tripolymeric Corneal Coating Gel Versus Balanced Salt Solution Irrigation During Cataract Surgery: A Retrospective Analysis - Giardini, Pietro (Cornea, 2018)
PURPOSE: To compare the protective properties and ease of manipulation during cataract surgery of corneal coating with a gel (eyeDRO; AL.CHI.MI.A. S.R.L, Italy) and corneal irrigation with balanced salt solution (BSS). METHODS: We analyzed the data of 51 patients receiving either eyeDRO or BSS during routine cataract surgery performed within a 20-day period in 2016. The selected parameters were intraoperative clarity and ease of manipulation; postoperative epithelial integrity; and patient discomfort. RESULTS: Compared with BSS irrigation, eyeDRO coating significantly increased intraoperative clarity and ease of manipulation (P < 0.01). Single application was required in eyeDRO-treated eyes, whereas BSS was applied 5.3 ± 0.4 times on average (P < 0.01). Two hours postoperatively, a normal epithelium was observed in 90.0% and 60.0% of eyeDRO-coated and BSS-irrigated eyes, respectively; punctate epithelial damage was observed in 9.7% and 40.0% (P < 0.05) of eyeDRO-coated and BSS-irrigated eyes, respectively; eye irritation and foreign body sensation were experienced by 13.0% and 37.0% of eyeDRO-treated patients and by 65.0% and 100% of BSS-treated patients, respectively (P < 0.01). Twenty-four hours postoperatively, 80.0% of BSS-treated patients versus 19.0% of eyeDRO-treated patients still experienced foreign body sensation (P < 0.01). CONCLUSIONS: EyeDRO coating was shown to be a safer and more effective option than BSS irrigation in cataract surgery because single application provided optimal hydration and intraoperative clarity during the entire surgery, better preserved the corneal epithelium, and offered postoperative comfort to the patient.